Flora of Aralam Wild Life Sanctuary - Dantas. K. J (Kerala Forest Research Institute Peechi, Thrissur, 2017)
The occurrence of three scapigerous Impatiens, I. dendricola, I. stocksii and I. lawsonii are reported for the first time from Kerala. I. dendricola and I. stocksii are so far known from the Karnataka part of Western Ghats and I. lawsonii from Nilgiris of Tamil Nadu. Conservation Status and intraspecific variations were reassessed based on the latest information.
Flora of Aralam Wild Life Sanctuary
Keywords: Balasaminaceae; Scapigerous; Impatiens; Western Ghats; Kerala